Two-Flap Technique, Superior Pedicle and Central Pedicle Retro Glandular Flap: Innovative Technique to Ensure Upper Pole Fullness after Breast Reduction Surgery - Gupta, Rajat; Bansal, Priya; Chaudhary, Gautam; Sharma, Shubham (Indian Journal of Plastic Surgery, 2025)
The two-flap technique, superior pedicle flap and central pedicle retro glandular (RG) flap, represents a novel advancement in breast reduction surgery, addressing issues such as upper pole deflation, asymmetry, and overall breast contour irregularities seen with traditional methods. This study evaluates the outcomes, efficacy, and safety of the two-flap technique, emphasizing its ability to provide enhanced aesthetic results and high patient satisfaction.A retrospective study was conducted on 165 patients who underwent the two-flap technique between February 2022 and February 2024. The technique involved preoperative skin markings for precise flap creation, using superior and central pedicles to ensure optimal vascularity and contour. Tissue reduction was performed based on individual patient needs, and post-surgical follow-ups ranged from 6 months to 1 year. Data collected included demographic details, tissue reduction volumes, postoperative complications, and patient satisfaction. Statistical analysis was conducted using SPSS software.The majority of patients (66.67%) were aged 31 to 40 years, with a mean age of 34.59 years. Tissue reduction ranged from 200 to 800 g, with 48.49% of patients having 200 to 400 g removed. Complications included seroma in 7.27% and wound dehiscence in 3.64%. Patient satisfaction was high, with 89.09% reporting being “highly satisfied.” The technique demonstrated significant improvements in upper pole fullness and breast contour.The two-flap technique offers a safe, effective, and aesthetically pleasing solution for breast reduction surgery. Its innovative approach minimizes complications and maximizes patient satisfaction, though further studies are recommended to validate its efficacy in larger breast sizes.
Keywords: two-flap technique; breast reduction surgery; upper pole fullness; breast aesthetics